Advanced performance analysis of the Illinois agility test based on the tangential velocity and turning radius in wheelchair rugby athletes - Usma-Alvarez, C. C.; Chua, J. J. C.; Fuss, F. K.; Subic, A.; Burton, M. (Sports Technology, 2010)
The Illinois agility test is a timed task suitable for wheelchair sports with multidirectional movements and it is commonly used to evaluate the agility performance of athletes. In addition to test times, tangential velocities and turning radii are parameters of high importance in the assessment of agility performance. The main objective of this study is to develop a method that allows the evaluation of the tangential velocity and turning radius that are achieved during the Illinois agility test, which is usually used for training wheelchair rugby athletes. A group of nine Paralympic wheelchair rugby athletes performed three trials of the Illinois agility test using their own custom made chairs. The wheelchairs were instrumented with a 6 DOF (degrees of freedom) sensor (accelerometer/gyrometer). Linear accelerations, angular velocities and test times were recorded during the test. The investigation of obtained performance enabled identification of instantaneous radii and tangential velocities of the turning chair for each of the 11 turns of the Illinois test. To evaluate an athlete`s performance, hypotheses based on optimisation strategy of performance for the test`s turning circuit were considered as follows: (1) athletes produce a longer rc in turns 3, 4, 5, 7, 8 and 9; (2) athletes produce a shorter rc (turning radius) in turns 2, 6 and 10; and (3) athletes produce a longer rc in turns 1 and 11. According to the performance parameters mentioned above, four performance quadrants could be identified for different turn radii and velocities. The performance assessment of athletes presented here showed no significant difference in turning radius between expected longer and shorter radius turns in individual athletes. It was concluded that using turning radius as a performance parameter is not appropriate. Velocity in the expected shorter radii proved to be generally larger than the one in the expected longer radii with significant difference in four of the nine athletes. Significant difference was found between radii of group A (low pointer athletes) and group B (mid pointer athletes), and larger radii were observed in group A (low pointer athletes). The differences in velocities between groups A and C, and between B and C were significant (P <= 0.001 each). The method developed and proposed proved to be valid for assisting performance assessment of wheelchair sports athletes using the Illinois agility test for training purposes. The study concludes that, in addition to test times, the use of instrumented chairs, a higher sample size and the application of the method presented are recommended for Illinois agility test assessment.